Onset and cessation of the rainy season on the Lake Titicaca slope - Rivas Meza, Niell Wilson (2024)
This study investigates the spatial and temporal variation of the rainy season on the slopes of Lake Titicaca by analyzing rainfall series extracted from the gridded database PISCOp V2.1 and 18 meteorological stations within the study area. The onset and end of the wet season from 1981 to 2012 were evaluated using gridded data, which were then validated with recorded rainfall data and performance statistical indicators. This methodology allowed the determination of the onset and end of the rainy season for each hydrological year of the study period, and the calculation of metrics such as rainy days, wet season rainfall, and rainfall intensity. The resulting time series were subjected to trend analysis, revealing that, in general, they did not exhibit statistically significant trends. This conclusion was also supported by the trend analysis of the series derived from the gridded data. The results highlight the importance of using validated gridded data for studying climatic patterns and accurately assessing the temporal variability of rainfall.